2017
DOI: 10.6002/ect.tond16.l10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hepatocellular carcinoma is the fifth most common tumor in patients worldwide and the third most common cause of cancer-related death, after lung and stomach cancer. Cirrhosis of the liver is the strongest predisposing factor for hepatocellular carcinoma, with approximately 80% of cases of hepatocellular carcinoma developing in a cirrhotic liver. The annual incidence of hepatocellular carcinoma is 2.0% to 6.6% in patients with cirrhosis compared with 0.4% in patients without cirrhosis. The 5-year survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Over 500,000 new HCC cases are diagnosed each year [ 1 ]. Viral hepatitis and nonalcoholic steatohepatitis are the most common causes of cirrhosis which underlies approximately 80% of cases of HCC [ 2 ]. HCC prognosis remains a challenge due to the recurrence of HCC and the 5-year overall survival rate is only 34 to 50% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 500,000 new HCC cases are diagnosed each year [ 1 ]. Viral hepatitis and nonalcoholic steatohepatitis are the most common causes of cirrhosis which underlies approximately 80% of cases of HCC [ 2 ]. HCC prognosis remains a challenge due to the recurrence of HCC and the 5-year overall survival rate is only 34 to 50% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCC is the fifth most common tumor in patients around the world and ranks third following lung cancer and gastric cancer among lethal cancers [20]. The results of this study revealed that SENP3-EIF4A1 was decreased in HCC tissues and plasma.…”
Section: Discussionmentioning
confidence: 58%
“…Most of the patients who end up developing HCC, would have had a background of established liver cirrhosis with varying risk factors. Viral hepatitis (hepatitis B and C), chronic alcoholism, and nonalcoholic fatty liver disease are the most common risk factors worldwide [1,5]. It is one of the leading causes of cancer death and has a high propensity for vascular invasion and metastasis at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%